(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This thesis embarks on a critical examination of the responsiveness of the Bureau of Fire Protection during fire disasters in Barangay Payatas, Quezon City. In doing so, it seeks to shed light on the strengths and weaknesses of the BFP’s disaster response strategies, with the ultimate aim of improving the community’s preparedness and resilience in the face of this ever-looming threat. Through an in-depth analysis of response times, resource allocation, training protocols, and community engagement, this research endeavor strives to contribute valuable insights to the broader field of disaster management and, more specifically, fire disaster response. The researchers will make use of a descriptive design that seeks to evaluate and assess the Responsiveness of the Bureau of Fire Protection during the Fire Disaster in Barangay Payatas, Quezon City. The researchers also used the purposive sampling technique to get their respondents among twenty (20) Bureau of Fire Protection Personnel and twenty (20) residents of Barangay Payatas, Quezon City, with a total population of forty (40) respondents. Researchers also used a researcher-made survey questionnaire containing questions related to our study, which can be answered with a 1 to 4-point rating scale. The outcome of the study about the Responsiveness of the Bureau of Fire Protection during a fire disaster in Barangay Payatas indicates that all of the respondents, including the BFP personnel, agreed with our study. The residents have answered and provided a rating that shows the BFP in Barangay Payatas is Effective and Responsive. The researchers also provide some measures to further develop and improve the responsiveness of the Bureau of Fire Protection in Barangay Payatas. The study found that the allocation of resources by BFP was often inadequate, leading to delays in controlling and extinguishing fires. Limited access to firefighting equipment and personnel was a key hindrance to rapid response. Therefore, the researchers conduct a comprehensive review of resource allocation within the Bureau of Fire Protection to ensure that an adequate number of firefighting equipment and trained personnel are available at all times and consider updating equipment as needed.